Security of Electronic Medical Information and Patient Privacy - Andriole, Katherine P.; Sings, Sings (Procedia of Engineering and Life Science, 2024)
Tujuan penelitian ini adalah untuk mengeksplorasi implementasi keamanan sistem Rekam Medis The responsibility that physicians have to protect their patients from harm extends to protecting the privacy and confidentiality of patient health information including that contained within radiological images. The intent of HIPAA and subsequent HIPAA Privacy and Security Rules is to keep patients’ private information confidential while allowing providers access to and maintaining the integrity ofrelevant information needed to provide care. Failure to comply with electronic protected health information (ePHI) regulations could result in financial or criminal penalties or both. Protected health information refers to anything that can reasonably be used to identify a patient (eg, name, age, date of birth, social security number, radiology examination accession number). The basic tools and techniques used to maintain medical information security and patient privacy described in this article include physical safeguards such as computer device isolation and data backup, technical safeguards such as firewalls and secure transmission modes, and administrative safeguards including documentation of security policies, training of staff, and audit tracking through system logs. Other important concepts related to privacy and security are explained, including user authentication, authorization, availability, confidentiality, data integrity, and nonrepudiation. Patient privacy and security of medical information are critical elements in today’s electronic health care environment. Radiology has led the way in adopting digital systems to make possible the availability of medical information anywhere anytime, and in identifying and working to eliminate any risks to patients.